Constructivistic-Based of Local Content Learning Model Design at SD Kristen Makale 1, Tana Toraja Regency - Dina Gasong; Tandiseru, Selvi (JTP - Jurnal Teknologi Pendidikan, 2022)
Local content learning in primary schools is very important. However, conditions during the COVID-19 pandemic require learning to be carried out from home. The purpose of this study is to design a local content learning model for Toraja Tallulolona culture in elementary schools based on constructivist networks. This research applies a qualitative descriptive method. Data obtained by means of (1) carry out learning in class V SD Kr Makale 1, (2) observing the implementation of local content learning Toraja Tallulolona Culture in the network, (3) do FGD. Data analysis was carried out qualitatively (1) identify learning components, (2) discussion of learning components, (3) drafting a learning model, (4) describes a learning model in the Constructivistic-based Toraja Tallulolona cultural local content network. The learning model designed, increases the learning motivation of Class V SD Kr. Makale V.